IS IT TUBERCULOSIS OR CROHN’S DISEASE? - Seerat, Iqtadar; Rafiq, Memona (Journal of Ayub Medical College Abbottabad, 2020)
Tuberculosis is very prevalent in countries like Pakistan. It can be a diagnostic challenge when it has extra pulmonary organ involvement. Variation in clinical signs and symptoms, lack of access to a specialist and limited financial resources often result in delayed diagnosis. This leads to an increase in overall morbidity and mortality. We are presenting a case of disseminated tuberculosis with predominant intestinal symptoms in an eleven years old boy. He remained undiagnosed for several years despite frequent visits to multiple general practitioners. After appropriate investigations and initiation of treatment for tuberculosis, he showed an excellent recovery. Keywords: Ileo-colonoscopy; Tuberculosis; Crohn’s Disease; Circumferential Ulcers